2014
DOI: 10.1093/infdis/jiu467
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Putative Artemisinin Resistance Mutations Among Plasmodium falciparum in Sub-Saharan Africa: A Molecular Epidemiologic Study

Abstract: Plasmodium falciparum parasites that are resistant to artemisinins have been detected in Southeast Asia. Resistance is associated with several polymorphisms in the parasite's K13-propeller gene. The molecular epidemiology of these artemisinin resistance genotypes in African parasite populations is unknown. We developed an assay to quantify rare polymorphisms in parasite populations that uses a pooled deep-sequencing approach to score allele frequencies, validated it by evaluating mixtures of laboratory parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

40
289
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(336 citation statements)
references
References 28 publications
40
289
4
3
Order By: Relevance
“…Similar observations have been made by a recent K13 genotyping study conducted in 14 African countries. 15 However, recent studies have shown a few examples of median parasite clearance half-life 5 hours in Democratic Republic of Congo and Nigeria. 11 Although factors other than parasite resistance could account for these observations, vigilant surveillance for initially low-prevalence resistance provides an important early-warning system for emerging or spreading resistance.…”
mentioning
confidence: 99%
“…Similar observations have been made by a recent K13 genotyping study conducted in 14 African countries. 15 However, recent studies have shown a few examples of median parasite clearance half-life 5 hours in Democratic Republic of Congo and Nigeria. 11 Although factors other than parasite resistance could account for these observations, vigilant surveillance for initially low-prevalence resistance provides an important early-warning system for emerging or spreading resistance.…”
mentioning
confidence: 99%
“…[7][8][9] Furthermore, other non-synonymous SNPs were identified in the sub-Saharan African samples that were not observed in the southeast Asian P. falciparum samples. These findings suggest that polymorphisms in the K13-propeller could vary geographically, and therefore, genetic studies on the K13-propeller in other malaria-endemic countries are needed to assess the use of this locus as a tool to monitor the global emergence and spread of artemisinin resistance.…”
mentioning
confidence: 99%
“…• studies of the distribution of polymorphisms in the field, particularly in Africa [9][10][11][12][13];…”
Section: A New Artemisinin Susceptibility Phenotype Arises In Asiamentioning
confidence: 99%